Effect of culture media composition on chitin content, nitrogen retention, crude fat digestibility, and growth of mealworms (Tenebrio molitor) - Nuraini, Nuraini; Alhidayat, Rizki; Rias, M. Ikhsan; Akbar, Muhammad (Jurnal Ilmu Peternakan Terapan, 2025)
The purpose of this study is to investigate how different culture media compositions affect Tenebrio molitor nutritional value. A Completely randomized design (CRD) including three treatments and six replications was the methodology employed at a significant level of 5%. Duncan's multiple range test (DMRT) was used to analyze the significant differences found. The treatments were T1 (100% CF), T2 (50% CF + 50% TD), and T3 (100% TD), which were various combinations of the commercial feed (CF): tofu dreg (TD). Chitin content, nitrogen retention, crude fat digestibility, feed consumption, weight gain, and feed conversion were the variables that were observed. The results indicated that changes in the culture media's make-up had a significant effect (P<0.01) on the mealworms' chitin content, nitrogen retention, feed consumption, weight gain, and feed conversion. However, there was no discernible change in crude fat digestibility (P>0,05). The best results were fou chitin content 9.61%, nitrogen retention rate 80.89%, a crude fat digestibility rate of 89.48%, feed consumption 264.88 g/1,000 larvae, weight gain 72.12 g/1,000 larvae, and a feed conversion rate 3.68.